Teachers’ Burnout and its Relationship to Schools Organizational Trust in Zarqa Governorate Schools as perceived by teachers - Al-Khalaileh, Huda; Al-Shayeb, Abd Elhafez; Saleh, Hadeel (Jordan Journal of Educational Sciences, 2012)
The study aimed at identifying the relationship between teachers’ burnout and school organizational trust in Zarqa Governorate schools. Data for this study were collected from (374) male and female teachers from (50) public schools which were randomly selected from all schools in Zarqa Governorate in the acadimc year 2009/2010. Faculty Trust Scale (FTS) and Maslach Burnout Inventory (MBI) were used to collect data from subjects. The results revealed a low level of teachers’ trust in students and parents but an accepted level of trust with principals and colleagues. On the other hand, the data showed that while teachers experienced high level of emotional exhaustion and personal accomplishment, they experienced a low level of depersonalization and a moderate level of general burnout. The significant negative correlations were found among (FTS) and MBI subscales. It has been found that teachers’ burnout decreases as trust level with their principals increases.